Culturable autochthonous gut bacteria in Atlantic salmon (Salmo salar L.) fed diets with or without chitin. Characterization by 16S rRNA gene sequencing, ability to produce enzymes and in vitro growth inhibition of four fish pathogens - Askarian, Fatemeh; Zhou, Zhigang; Olsen, Rolf Erik; Sperstad, Sigmund; Ringø, Einar (Aquaculture, 2011)
The present investigation evaluated the effect of chitin (5% supplementation) on the adherent aerobic intestinal microbiota of Atlantic salmon (Salmo salar L.). One hundred and seventy three isolates were isolated but 34 isolates died prior to positive identification. Sixty four out of 139 autochthonous gut bacteria were further identified by 16S rRNA gene sequencing and further tested for protease, amylase, cellulase, phytase, lipase and chitinase activities. Moreover, the most promising enzyme-producing bacteria and intestinal lactic acid bacteria (LAB) were tested for in vitro growth inhibition of four important fish pathogens: Aeromonas salmonicida subsp. salmonicida, Vibrio (Listonella) anguillarum, Moritella viscosa and Carnobacterium maltaromaticum. Dietary chitin modulates the gut microbiota but not the portion of enzyme-producing gut bacteria. LAB were only isolated from fish fed the chitin supplemented diet and they were able to inhibit in vitro growth of 3 of the 4 pathogens. However, the most promising gut bacteria isolated in the present study with respect to enzyme production and in vitro growth inhibition showed high similarity to Bacillus thuringiensis by 16SrRNA gene sequencing.